Lexical Paraphrases in Tonis (a Poetry of Dawan or Uab Meto) Marriage Process in South Central Timor District - Isu, Rudolof J. (Universitas Negeri Semarang, 2024)
This paper is entitled Lexical Paraphrase in Tonis (Dawan Poetry or Uab Meto) used in the Marriage Process in South Central Timor District. The problem of this paper is whether the speech in tonis in Dawan ethnic can show lexical paraphrase both lexical paraphrase on noun, lexical paraphrase on adverb, lexical paraphrase on adjective and lexical paraphrase on preposition. The purpose of this research is to find out whether there is a paraphrasing process in the speech of the marriage process in South Central Timor District. The topic or title mentioned above is considered to have its own uniqueness in language style and distinctiveness in speech. This research uses a qualitative approach method. The results of this study show that there are fifty lexical paraphrases on verbs, twenty-four lexical paraphrases on nouns, eleven lexical paraphrases on adverbs, four lexical paraphrases on adjectives, and one lexical paraphrase on prepositions